A review of liver fibrosis and cirrhosis regression - Michael J. Lee (Korean Society of Pathologists & the Korean Society for Cytopathology, 2023)
Cirrhosis has traditionally been considered an irreversible process of end-stage liver disease. With new treatments for chronic liver disease, there is regression of fibrosis and cirrhosis, improvement in clinical parameters (i.e. liver function and hemodynamic markers, hepatic venous pressure gradient), and survival rates, demonstrating that fibrosis and fibrolysis are a dynamic process moving in two directions. Microscopically, hepatocytes push into thinning fibrous septa with eventual perforation leaving behind delicate periportal spikes in the portal tracts and loss of portal veins. Obliterated portal veins during progressive fibrosis and cirrhosis due to parenchymal extinction, vascular remodeling and thrombosis often leave behind a bile duct and hepatic artery within the portal tract. Traditional staging classification systems focused on a linear, progressive process; however, the Beijing classification system incorporates both the bidirectional nature for the progression and regression of fibrosis. However, even with regression, vascular lesions/remodeling, parenchymal extinction and a cumulative mutational burden place patients at an increased risk for developing hepatocellular carcinoma and should continue to undergo active clinical surveillance. It is more appropriate to consider cirrhosis as another stage in the evolution of chronic liver disease as a bidirectional process rather than an end-stage, irreversible state.